Edible Mushrooms of Peri-Urban Kichwa Communities in the Andes-Amazon Piedmont, Ecuador - Vicente Pérez, Katia Stefanía (2024)
Ecuador is a multicultural and megadiverse country where nearly 50 species of wild edible macrofungi (WEM), used by 12 indigenous peoples, have been reported. The Kichwa use 29 species of mushrooms, but aspects of their ecology are unknown. The aim of this study was to study the richness, use, substrates and fruiting seasons of WEM consumed by two peri-urban Kichwa communities settled in the piedmont between the Andes and the Amazon. Between May 2019 to April 2020, we conducted 56 interviews with adults and 12 walks in the chagras and forests. People recognized 26 fungal names related to 12 species of mushrooms, 11 basidiomycetes and one ascomycete. Three species were the most culturally important: Favolus tenuiculus, Bresodolia paradoxa and Lentinus concavus, defined by their abundance, economic importance and taste. Six mushroom species were newly reported for the Kichwa group and four species added to the list of species in the country. All the fungi were lignicolous; they were found on the trunks of 16 species of plants in the chagras. The plant-trees: P. discolor, Inga edulis and C. alliodora were the most common substrates. These species are abundant in the chagras and frequently used for their wood. Ecological and traditional knowledge related to WEM is important to enhance management practices in situ and ex situ.